BIOLOGICAL VALUE OF COW MILK AND COTTAGE CHEESE OF UKRAINIAN BLACK-AND-WHITE DAIRY BREED WITH DIFFERENT GENOTYPES OF KAPPA-CASEIN (CSN3) - Polieva I. О.; Korh, I. V.; Karunna, T. I.; Tenditnyk, V. S.; Kodak, T. S. (Scientific Progress & Innovations, 2021)
The article presents experimental data on the study of amino acid composition and amino acid score of milk of Ukrainian Black-and-White dairy cows with different genotypes of kappa-casein. The aim of the study was to identify the link between the kappa-casein gene (CSN3) and the biological value of milk and cottage cheese of the Ukrainian Black-and-White dairy cows breed. The research was conducted at “Profin-tern” branch of the breeding plant for breeding the Ukrainian Black-and-White dairy breed of the state en-terprise “Hontarivka” of the Institute of Animal Science of the National Academy of Agrarian Sciences of Ukraine. The processing of the obtained results and the analytical part were carried out on the research base of the Testing Center of the Institute of Animal Science of NAAS.To conduct the scientific and economic experiment, a group of dairy cows of the Ukrainian Black-and-White breed was formed – 95 heads. Gene polymorphism analysis was conducted by PCR – RFLP method. According to the results of DNA testing for the kappa-casein gene (CSN3), the selected herd was divided into three groups of cows with genotypes: AA; AB and BB. The identification of milk and sour milk cheese amino acid spectrum was performed in five dried out samples from each subgroup of cows on the basis of RUЕ “The Scientific and Practical Center of the National Academy of Sciences of Belarus for Animal Husbandry”, by the method of liquid chromatography using the automatic amino acid analyzer of Hitachi-8900 brand, according to ISO 13903 requirements. Quantitative assessment of the amino acid composition of milk and cottage cheese was given by the total amount of essential and replaceable amino acids in 1 g of protein. The amino acid index was calculated by the ratio of essential to replaceable amino acids. As a result of the conducted researches, it has been estab-lished that the cows with the genotype of CSN3BB of kappa-casein there had the tendency to increase the ratio of essential amino acids to replaceable ones in comparison with AA and AB animal genotypes by 9.0 and 5.9 %, respectively. When assessing the compliance of milk biological value of the experimental cows with the preferable protein according to the FAO/WHO scale, it should be noted that it was of better quality in animals with CSN3BB genotype. The protein of cottage cheese made from cow milk, regardless of the geno-type, was poor in essential amino acids. The scores of all essential amino acids ranged from 47.1 % to 124.9 %. It has been found that the milk of BB cow genotype as to the amino acid index and the score of ideal protein was characterized as a product of high biological value. It has been revealed that due to the balanced concentration of essential and non-essential amino acids in the protein of sour milk cheese made from milk of cows with AB and BB genotypes, its nutritional and biological value increased in comparison with animals with AA genotype.